Satire Content Youtube’s Got Talent Channel Skinny Indonesia24 Perspektif Etika Dan Komunikasi Islam - Sulvina Jayanti; Afidatul Asmar; Saukani, Muhammad Saukani (Communication and Islamic Broadcasting Studies IAIN Parepare, 2023)
Satire Content Youtube's Got Talent Channel Skinny Indonesia24 Perspective of Islamic Ethics Freedom in uploading YouTube content is one of the reasons for the decline in content quality. This phenomenon was criticized by skinnyindonesia24 by creating YouTube's got talent content to criticize YouTube content which is considered to lower the standard of YouTube creator content. The purpose of this study was to examine the meaning and find out the satire from the perspective of Islamic ethics and communication on YouTube's got talent. This study uses descriptive discourse analysis by analyzing the three parts of YouTube's got talent content to obtain research data. The data collection technique in this study was carried out through the observation stage by watching repeatedly and documentation by taking screenshots of the atmosphere and dialogue relevant to this research. The results of this study indicate that the soft satire and hard satire used have a meaning of criticism of YouTube content which is considered to lower the standards of content creators. In this content there are also several dialogues that are not in accordance with communication ethics such as nature, actions, morals and relationships. Several dialogues also come out of the principles of Islamic communication and communication